Exploiting group symmetry in semidefinite programming relaxations of the quadratic assignment problem - de Klerk, Etienne; Sotirov, Renata (Mathematical programming, 2010)
We consider semidefinite programming relaxations of the quadratic assignment problem, and show how to exploit group symmetry in the problem data. Thus we are able to compute the best known lower bounds for several instances of quadratic assignment problems from the problem library: (Burkard et al. in J Global Optim 10:291–403, 1997).